TOWARDS A CHRISTIAN THEOLOGY OF AFRICAN RELIGION: Issues of Interpretation and Mission (Hekima Review, 2006)
This book is another volume added to the already abundant existing literature on African Traditional Religion. One may even think that writing another volume on it is superfluous. While theologians like Okot P’Bitek, John Mbiti, Geoffrey Parrinder, treated the question of African Traditional Religion rather phenomenologically and anthropologically, and Emmanuel Idowu Bulagi and Laurent Magesa treated it more theologically, Francis Oborji treats it both theologically and with a deep sense of mission within the context of inculturation. In fact, the uniqueness of his work lies in the very title, which indicates to us the effort of the author to develop an authentic Christian theology of African Traditional Religion and with a specific missiological orientation, the issue of interpretation and mission.